Clinical outcomes of advanced-stage cutaneous lymphoma under low-dose gemcitabine treatment: real-life data from the German cutaneous lymphoma network - Blazejak, Christoph; Stranzenbach, René; Gosman, Janika; Gambichler, Thilo; Wehkamp, Ulrike; Stendel, Sarja; Klemke, Claus-Detlev; Wobser, Marion; Olk, Joanna; Nicolay, Jan Peter; Weyermann, Maria; Stadler, Rudolf; et al. (Dermatology, 2022)
Background: Gemcitabine is an effective single-agent chemotherapy used in advanced stages of cutaneous T-cell lymphoma (CTCL). However, gemcitabine used in the current standard regimen is frequently associated with adverse events (AE), such as an increased risk for myelosuppression and severe infections. Objectives: We investigated in this retrospective study the effect of low-dose gemcitabine in pretreated advanced-stage CTCL and in blastic plasmacytoid dendritic cell neoplasia (BPDCN) regarding overall response (OR), progression-free survival (PFS), and AE. Material and Methods: A retrospective, multicenter study was conducted on 64 CTCL and BPDCN patients treated with gemcitabine in average absolute dosage of 1,800 mg/m2 per cycle, which is 50% lower compared to standard dosage of 3,600 mg/m2 per cycle (1,200 mg/m2 day 1, 8, 15). Evaluation of response to therapy and AE was done 4-6 weeks after the sixth cycle. Results: OR was 62% with 11% demonstrating a complete response. The median time of PFS was 12 months and median time to next treatment was 7 months. Only 3/63 patients showed serious side effects, e.g., port infection or acute renal failure. Almost 73% of the patients experienced minor to moderate side effects (CTCAE grade 0-2). Fatigue (27.2%), fever (22.7%), and mild blood count alteration (18.2%) were the most common AE. Conclusions: This retrospective analysis supports the use of low-dose gemcitabine therapy in CTCL, demonstrating with 62% OR and PFS of 12 months an almost identical response rate and survival as compared to the standard dose therapy reported in previous studies but with a significantly improved safety profile and tolerability.
Gesehen am 16.12.2022